Sistem Pendukung Keputusan Penerimaan Prodeo Pada Pengadilan Agama Medan Kelas I A Menerapkan EXPROM II - Feronika Sitinjak, Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
– Prodeo is a court litigation process for free with state funding through court DIPA (Article 1 paragraph 7). In receiving assistance for the general public, it is very important to know how the case is and so that the recipients of the aid can be right on target, there is no choice. In determining the acceptance of Prodeo Medan Religious Court Class 1 A, still using manual methods or there is no system to determine the receipt of a computerized prodeo. So with that the authors propose a computerized system in determining the acceptance of Predeo at the Medan Class 1 A Religious Court.The method that the author proposes in determining the Prodeo Recipient at the Medan Class 1 A Religious Court is the EXPROM II Method, namely the comparison of deviation or distance between alternative pairs for each criterion. In this method, the relative value of one of the alternatives is defined by two preference indices. So the procedure for admission of prodeo at the Medan Religious Court Class I A produces values ​​that can provide an overview in decision making, in order to get the right results for the acceptance of prodeo.